PENINGKATAN LITERASI PENGELOLAAN SAMPAH BERBASIS AKUNTANSI LINGKUNGAN PADA KELURAHAN - KELURAHAN KOTA CIMAHI - Citra Mulyandini, Vita; Kustinah, Siti; Winarso, Eddy; Jayanti, Dwi; Romli; Marlina; Prasetio Adi, Patria; Nidyati, Adelia (ABDI DALEM: Jurnal Pengabdian Kepada Masyarakat, 2025)
Waste management is one of the major challenges faced by urban communities, including those in Melong and Cimahi sub-districts. The lack of public literacy in sorting, managing, and understanding the economic value of waste has led to an increasing volume of waste and low community participation in sustainable environmental management. To address this issue, this community service program was carried out with the aim of improving waste management literacy based on environmental accounting. The approach introduced the concept of recording the economic value of waste, the role of waste banks, and transparency in management through simple recording systems. The methods included education through training sessions, group discussions, and recording simulations. Evaluation was conducted using pre-test and post-test questionnaires with seven main indicators: waste knowledge, waste sorting, understanding of environmental accounting, recording economic value, the role of waste banks, environmental awareness, and transparency. A total of 63 participants from both sub-districts were involved.The results show a significant improvement in participants’ literacy, with the average pre-test score of 55 increasing to 82 in the post-test. The indicator of understanding environmental accounting showed the highest increase, from 47% to 83%. These findings demonstrate that the application of environmental accounting can enhance awareness, participation, and social responsibility in community-based waste management.